2020
DOI: 10.1080/02713683.2020.1725062
|View full text |Cite
|
Sign up to set email alerts
|

Microdot Accumulation in the Anterior Cornea with Aging – Quantitative Analysis with in Vivo Confocal Microscopy

Abstract: Purpose: Degenerative 'microdot' deposits in healthy and hypoxic corneas are believed to represent lipofuscin-like material aggregation in the stroma. To accurately assess microdot deposits in a clinical setting, we sought to quantify these deposits for the first time using the non-invasive clinical imaging technique of in vivo confocal microscopy (IVCM). Methods: The corneas of 102 healthy subjects aged 15-88 years were examined by IVCM and microdot density was quantified using a 6-point grading scale by two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…They have been reported in healthy subjects and are regarded as early-stage irreversible corneal stromal alterations due to hypoxia [ 42 ]. Utheim et al reported an accumulation of microdots in the aging cornea, primarily in the subepithelial stromal region [ 43 ]. This conclusion does not align with our findings, since P5 is young (13 years old) and presented with microdot accumulation in the anterior and posterior stroma.…”
Section: Discussionmentioning
confidence: 99%
“…They have been reported in healthy subjects and are regarded as early-stage irreversible corneal stromal alterations due to hypoxia [ 42 ]. Utheim et al reported an accumulation of microdots in the aging cornea, primarily in the subepithelial stromal region [ 43 ]. This conclusion does not align with our findings, since P5 is young (13 years old) and presented with microdot accumulation in the anterior and posterior stroma.…”
Section: Discussionmentioning
confidence: 99%
“…Confocal microscopy might be superior to specular microscopy to analyze the endothelial cells in AACC with corneal edema. The confocal microscope can directly obtain images of tissues and cells in each layer of the cornea through continuous confocal scanning, detecting various elements of normal and affected corneas in multiple layers and in vivo, without fixation and staining of tissue sections [9][10][11][12][13][14]. Thus, it is a major method for exploring the pathological mechanism of ophthalmic diseases at the cellular level.…”
Section: Discussionmentioning
confidence: 99%
“…Specular microscopy should be performed for glaucoma patients to check the endothelial cell density before intraocular surgery, but corneal edema caused by acute IOP elevation often makes it impossible to analyze the endothelial cells [7,8]. Confocal microscopy is a novel non-invasive corneal imaging examination method [9][10][11]. Due to high resolution and magnification, it reveals the corneal changes at the cellular level under three-dimensional space and real-time conditions; similar results could be obtained in the cloudy corneal tissue, making it a commonly used tool for the clinical study of corneal lesions [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations